The challenges faced by nursing professionals facing COVID-19 (Research, Society and Development, 2021)
The objective of this work was identifying the challenges faced by nursing professionals during the COVID-19 pandemic. This is an integrative review study with a qualitative approach, a literature review of articles published in the Scientific Electronic Library Online (SCIELO), Virtual Health Library (BVS), National Library of Medicine, National Institutes of Health (PUBMED) databases ), Caribbean Latin American Literature on Health Sciences (LILACS), the selection and screening process of the studies was carried out through the thorough reading of titles and abstracts, following the previously established selection criteria, which were: articles for online access open, in the Portuguese language and which included the health professionals who worked on the frontline of COVID-19, with an emphasis on the nursing team. For the initial research 42 articles were used, after reading in full, 33 articles were excluded, leaving 9 articles according to their relevance for the integrative review. From the analyzed and selected articles, the authors elaborated a table that includes information from the studied articles, such as: title, authors, year of publication, population and the results presented. The multidisciplinary team that makes up the health system, especially nursing, experienced a challenging moment with the emergence of COVID-19, such challenges caused several problems for these workers, among them the most mentioned psychological disorders.